2017
DOI: 10.3892/etm.2017.5173
|View full text |Cite
|
Sign up to set email alerts
|

An integrated bioinformatical analysis of miR‑19a target genes in multiple myeloma

Abstract: MicroRNA (miR)-19a, as an oncomiR, has been studied in several types of cancer; however, its role in the development and progression of multiple myeloma (MM) remains unclear. The present study used a bioinformatics approach to investigate the involvement of miR-19a in MM. miR-19a targets were predicted using target prediction programs, followed by screening for differentially expressed genes in MM. The function of these genes was then annotated using gene ontology term enrichment, signaling pathway enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…miRNAs regulate gene expression at a posttranscriptional level by degrading or repressing target mRNAs, resulting in translational repression or mRNA degradation. 16,17 Our previous study reported that miR199a-5p suppresses glioma cell proliferation, migration, and invasion by inhibiting MAGT1. 18 However, the correlation between CELSR1 and miR-199a-5p has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate gene expression at a posttranscriptional level by degrading or repressing target mRNAs, resulting in translational repression or mRNA degradation. 16,17 Our previous study reported that miR199a-5p suppresses glioma cell proliferation, migration, and invasion by inhibiting MAGT1. 18 However, the correlation between CELSR1 and miR-199a-5p has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In oncology NLP is used for identifying disease stages [16], and evaluating outcomes (such as adverse drug reactions [17] or tumor recurrences [18]). Other NLP projects targeting MM take into account performance to identify genes associated with MM [19], “a standardized hierarchic ontology of cancer treatments” [20] or an “ontology-driven semiological rules base and a consultation form to aid in the diagnosis of plasma cells diseases” [21].…”
Section: Discussionmentioning
confidence: 99%
“…But the difference between AAAAAA and UUUUUU is significantly larger than between AAAAAA and AAAAAC . Therefore, we introduce natural language processing technology to solve this problem [3538]. It can not only transform the original high-dimensional data into low-dimensional continuous real-valued vector, but also learn its effective representation from miRNA sequences in an unsupervised manner.…”
Section: Methodsmentioning
confidence: 99%